Teachers’ and tutors’ social reflection around SenseCam images - Fleck, Rowanne; Fitzpatrick, Geraldine (International journal of human-computer studies, 2009)
As photographic technologies continue to develop, so too do the social practices surrounding their use. The focus of this paper is on the social practices surrounding images captured from a new photographic device—SenseCam—which, rather than capturing individual images when triggered by the user, automatically captures a series of images. This paper is concerned with the use of SenseCam digital images in social contexts where there is a professional purpose—supporting the collaborative reflective practices of school teachers and university tutors as part of their professional development. Analysis of video data collected from 16 in-situ case studies of reflective discussions shows evidence that reflection took place as defined in the literature. Further the phototalk around SenseCam images was found to benefit reflection in these social situations through promotion of a rich shared understanding of the lesson context: supporting return to the experience, sharing of background context, grounding conversations, illustrating and providing evidence, and allowing people to see more. The paper concludes with a discussion on how different features of SenseCam images, such as variable quality, lack of audio and incompleteness, helped in this reflection or not. Finally implications from this work and participant's comments are used to suggest ways in which SenseCam may be used in the future in teachers’ and tutors’ social reflection.